2018
DOI: 10.4028/www.scientific.net/kem.770.155
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges Associated with the Formation of Equiaxed Grains during Additive Manufacturing of Titanium Alloys

Abstract: It is well established that columnar grain structures usually form when metal alloys are used to additively manufacture components. A challenging goal is to produce an equiaxed grain structure throughout the component to remove anisotropy and refine the grain size in order to improve its mechanical performance. The high cooling rates and associated high temperature gradients are the main reasons for the formation of columnar grains via epitaxial growth of each added layer of material. There appear to be limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…[21][22][23][24] However, there are limited reports of incorporating the model with AM solidification conditions. [25,26] In addition, the interaction of multiple thermal cycles during AM makes the solidification process more complex than conventional solidification processing.…”
Section: Metal Fusion Additive Manufacturing (Am) Ismentioning
confidence: 99%
“…[21][22][23][24] However, there are limited reports of incorporating the model with AM solidification conditions. [25,26] In addition, the interaction of multiple thermal cycles during AM makes the solidification process more complex than conventional solidification processing.…”
Section: Metal Fusion Additive Manufacturing (Am) Ismentioning
confidence: 99%
“…Generally, deep dimples are attributed to the decrease of resistance to dislocation sliding. [ 34,35 ] However, the size of dimples became shallower, and the number of secondary cracks increased with boron addition (Figure 10d–f). As reported by Zhang et al, [ 27 ] the excess TiB particles in Ti–6Al–4V manufactured by direct laser deposition embrittled the alloy and reduced the ductility.…”
Section: Resultsmentioning
confidence: 99%
“…The widths of α laths have been observed to influence the yield strengths of additively manufactured Ti-6Al-4V structures in accordance with the Hall-Petch relationship[71]. Since the β phase influences α-colony size and orientation, the lower widths of the prior-β grains in the longitudinal direction may have increased the yield strength in that direction[39].…”
mentioning
confidence: 63%
“…It was identified that, to refine AM samples to the same degree as cast microstructures, a potent nucleant must be identified that can work in conjunction with the solutes. These findings led to a publication by StJohn et al [39] that focused on the challenges of obtaining an equiaxed microstructure during the additive manufacturing of titanium. This publication utilised research conducted as part of this candidature as a foundation to determine conditions that promoted the growth of equiaxed grains during AM.…”
Section: Chapter 6 Outcomes Conclusion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation